"I Wanted to Give Back to the Profession:" Preservice Teacher Supervision as Service Work. (2nd January 2022) - Capello, Sarah
ABSTRACT: For decades, university supervisors of preservice teachers (PSTs) have been undervalued and ignored. Following neoliberal reforms, post-secondary institutions have outsourced PST supervision to contingent faculty, failed to provide professional development for supervisors, offered poor employment conditions, and overlooked PST supervision in tenure and promotion decisions. These actions, combined with the service orientation of teacher education, have framed PST supervision as service work. This case study sought to understand how supervisors and administrators in one teacher education department positioned supervisors' work as service and the influence of the institution and department on that positioning. Using a survey, interviews, and document analysis, this study found that supervisors positioned their work as professional, financial, and emotional service. In turn, the institution and teacher education department positioned supervisors' work as service by providing minimal compensation and no institutional rewards and expecting supervisors to enact roles that were not officially required of them. The study's implications are that teacher educators and higher education administrators should strive to recruit and retain a professional corps of supervisors, provide ongoing professional development to supervisors to assist in the professionalization of the role, and resist notions of supervision as service.